Pharmacy Student Perceptions of the Roles and Attributes of Pharmacist Preceptors in Australia - Gillian J. Knott; Martina F. Mylrea; Beverley D. Glass (MDPI AG, 2022)
The pharmacist preceptor is key to the success of pharmacy student experiential placements with a recent focus being placed on the quality of preceptors. This study sought to investigate student perceptions of the ideal roles and attributes of pharmacist preceptors to inform the development of a preceptor training program. This was a mixed methods study using an online survey of pharmacy students from levels two to four of an undergraduate pharmacy honours program at a regional Australian university followed by qualitative, semi-structured focus group interviews. Surveys were analysed using descriptive statistics and content analysis while interviews were thematically analysed. Thirty-seven complete survey responses were received, and three student focus groups were conducted. Students identified the key role of preceptors in linking theory to practice and felt that the role of the preceptor in student assessment should focus on practical skills, such as communication and professionalism. There was overall strong agreement between the quantitative and qualitative findings on the ideal preceptor attributes with good communication, enthusiasm for the profession and the provision of clear and honest student feedback thought to be most important. Students regarded these attributes as essential for a good preceptor-student relationship to promote learning in the practice environment.